Pengaruh Motivasi Kerja, Pengembangan Karyawan, dan Kompensasi terhadap Turnover Karyawan pada Perusahaan PT LKMAK - Bela Annisa Rizqika Mufti; Albert Surya Wanasida (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the influence of work motivation, employee development, and compensation on employee turnover at PT LKMAK. A quantitative approach was employed, utilizing Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The findings reveal that work motivation and employee development have a negative effect on turnover, indicating that increased motivation and the availability of relevant development programs can reduce employees’ intention to leave the organization. In contrast, compensation shows a positive effect on turnover, suggesting that increasing financial rewards without sufficient support from intrinsic and non-financial factors may lead to higher turnover intention. These results underscore the importance of strategically managing motivation and employee development, as well as designing a fair compensation system to effectively minimize employee turnover.